Ivan Argunov’s Portrait of Anna Kalmykova - Alexandra Helprin (Вивліоѳика)
This article examines Ivan Petrovich Argunov’s 1767 painting of Anna Nikolaevna Kalmykova, one of many Kalmyk children removed from their families by the Russian military and forcibly adopted by elite Russians and Europeans. Both sitter and painter were, in different ways, unfree: Argunov was enserfed by the Sheremetev family and Kalmykova was their ward. Examining the portrait’s many visual antecedents and references, this paper argues that Argunov used the intimate, informal styles of Enlightenment portraiture in a way that enmeshed its subject and author in the harsh social hierarchies of the Sheremetev household and imperial society. The relatively loose facture of the painting and its attention to the sitter’s liveliness and youth demonstrate Argunov’s skill as a modern portraitist. But although Kalmykova dominates the composition of her own portrait (which makes it unlike most other portraits of Kalmyk people in Russia during this period), Argunov makes clear that she is subordinate to her patron and other members of her “adoptive” family. Mapping the power structures of the household that enserfed him, Argunov combined private and ceremonial idioms in a way that said much about Kalmykova’s status and his own – a manner of portraiture that could only be copied by other artists from outside the household.